Intrinsic work values on building association of South-East Asian Nation’s future workforce: a comparison of three nations - Mohamad, Bahtiar; Zulkepli Hew, Jafri; Ismail, Ahmed Rageh; Abu Bakar, Hassan (2016)
The aim of this study is to examine the intrinsic work values that were perceived by the university undergraduates in the three nations (Malaysia, Thailand and Indonesia) to influence cooperative communication.These three nations are among the founders of Association of South-East Asian Nations (ASEAN) in 1967 that represents half of the population of the region.Intrinsic work values are an important medium through which employee behavior can be understood and managed. Previous research suggests that intrinsic work values influences cooperative communication; the relationships among these constructs, however, have not been portrayed explicitly in a theoretical model, nor have they been empirically tested.Therefore, it is important to identify the dimensionality of intrinsic work value in ASEAN future workforce and assess an empirical conceptual framework of the relationships between work values and cooperative communication. The study uses an ASEAN university’s student sample from three nations for comparative study. Using a simultaneous multiple regression analysis, the contribution of six intrinsic work values factors in creating cooperative communication in the three ASEAN nations was assessed.The findings show that intrinsic work values do impact upon cooperative communication for Malaysia, Thailand and Indonesia.The paper draws attention to intrinsic work values of ASEAN university’s student who is considered as future employees in this region